2015
DOI: 10.14260/jemds/2015/390
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Effect of Two Different Doses of Dexmed E Tomidine on Haemodynamic Response to Laryngoscopy and Endotracheal Intubation

Abstract: OBJECTIVE OF THE STUDY:To compare the effectiveness of two different doses of Dexmedetomidine, 0.6μg/kg body weight and 1μg/kg body weight in attenuating haemodynamic response to laryngoscopy and endotracheal intubation. MATERIAL AND METHODS: 90 ASA Class 1 patients posted for elective surgery divided into 3 groups, Group DX-0.6 receive Dexmedetomidine, 0.6μg/kg body weight Group DX-1 receive Dexmedetomidine, 1μg/kg body weight and Group CT receive normal saline. The HR, SBP, DBP, MAP recorded at different int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Thiopentone and Isoflurane as an inhalational agent. Rashmi et al 2013 [13] compared the two different doses of Dexmedetomidine, 0.6μ g/kg and 1μ g/kg and control group of NS. As seen in our study they also found fall in DBP after the start of Dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…Thiopentone and Isoflurane as an inhalational agent. Rashmi et al 2013 [13] compared the two different doses of Dexmedetomidine, 0.6μ g/kg and 1μ g/kg and control group of NS. As seen in our study they also found fall in DBP after the start of Dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%